Analize Exchange Rate Changes effect on Poverty in Iraq for the Period (2004-2022) - Taleb, Ashraq; Hasan Abu-Nayla, Azhar (Journal of Economics and Administrative Sciences, 2024)
Purpose: Analysis of the Impact of Exchange Rate Changes on the Poverty Index in Iraq and a Study of the Resulting Effects for the period (2004-2022).Theoretical framework: The research studied the relationship between the change in the (EX) and its role in reducing the phenomenon of poverty in Iraq for the period (2004-2022). The exchange rate is considered one of the most important tools of monetary policy in the Iraqi economy due to its sensitivity to any change taken by the monetary authority and its direct and indirect effects on all economic variables, including its impact on the poverty rate.Design/methodology/approach: The researcher relied on the deductive (inductive) approach and the inductive approach based on theoretical foundations by employing the descriptive analysis method and using all data, parameters, and the measurement tool (E-views 13) to measure changes in exchange rates and its role in reducing the phenomenon of poverty in Iraq, and the data extended for the period from 2004-2022.Findings: It became evident that there is a long-term equilibrium relationship between the dependent variable, poverty rate, and the independent variables represented by the official exchange rate and imported inflation.Research, Practical & Social Implications: This research examines how exchange rate fluctuations impacted poverty in Iraq from 2004 to 2022, highlighting the practical challenges and social consequences for vulnerable populations and economic stability in Iraq.Originality/value: This study provides the correlation between exchange rate fluctuations and poverty in Iraq from 2004-2022, offering new perspectives on economic vulnerability and policy responses.